Human Immunodefeciency Virus Associated Cryptococcal Meningitis At A Tertiary Care Centre: Diagnostic Tools And Antifungal Susceptibility Testing - Munivenkataswamy, Rashmi (Journal of clinical and diagnostic research, 2013)
Cryptococcal meningitis has emerged as a leading cause of the infectious morbidity and mortality in HIV sero-reactive subjects and it is the second most common cause of the opportunistic neuroinfections in it. As this is a indistinguishable from other causes of meningitis, its early diagnosis is the key to the therapeutic success. This study was undertaken to know the incidence of Cryptococcal meningitis in HIV sero-reactive individuals and to assess the role of the microbiological parameters in its specific diagnosis, with a perspective of evaluating the anti-fungal resistance. A total of 66 CSF samples from suspected cases of meningoencephalitis were subjected to standard microbiological procedures. The Cryptococcal isolates were identified by microscopy, the cultural characteristics, melanin production on Niger Seed agar, urea hydrolysis, the Nitrate assimilation test and by capsular antigen detection by latex agglutination. The Cryptoccal isolates were further biotyped by using Canavanine-Glycine-Bromothymol blue agar. The Minimum Inhibitory Concentrations (MIC) of Amphotericin B and Fluconazole for the isolates were detected. The incidence of Cryptococcal meningitis in our study group was 18.2% (12/66). The Cryptococcal antigen was detected in all the 12 cases, whereas microscopy was positive only in 9 cases and Cryptococcus was isolated by culture in 10 cases. All the isolates were sensitive to Amphotericin B and 90% of the isolates were sensitive to Fluconazole. The CD4counts ranged between 22-138 cells /μl. A high incidence of Cryptococcal meningitis in HIV sero-reactive subjects necessitates the importance of a precise and an early microbiological diagnosis for better management of such subjects. Due to the growing concern of emerging drug resistance, the testing for the anti-fungal susceptibility has to be encouraged in all the cases.